Stages of E-Government maturity models: emergence of E-Governance at the Grass Roots - Rahman, Md. Hakikur (2013)
E-Government and e-Governance are the two terms within the governance system that need to be attended through clarity, distinctness, and justification. No matter how the stages of the governance system evolve, where they have been applied, and in which stages they are at a present moment, these two prominently distinct elements of the governance systems are yet to be watched closely and minutely. After synthesizing existing e-Government maturity models and exploring relevant literature, this chapter proposes a new model that may guide e-Government implementation in a developing world context. It is expected that the proposed model would assist researchers, academics, and policy makers in establishing sustained e-Government model in emerging and developing economies.